硬件加速器的性能测量的方法、系统和计算机可读介质 (2018)
硬件加速器的性能测量，其中个或多个计算机处理器可操作地耦接到至少个硬件加速器，并且计算机存储器可操作地耦接到个或多个计算机处理器，包括由个或多个处理器操作处于饱和状态的加速器，由处理器以使得加速器的数据处理资源饱和的速率向加速器提交数据处理任务，从而使加速器拒绝所提交的任务中的至少些；以及在加速器以饱和状态操作时，由处理器根据加速器接受多个提交的任务所经历的时间段来测量加速器性能。 Performance measurement of hardware accelerators, where one or more computer processors are operably coupled to at least one hardware accelerator, and a computer memory is operatively coupled to the one or more computer processors, including operating by the one or more processors the accelerator at saturation, submitting data processing tasks by the processors to the accelerator at a rate that saturates the data processing resources of the accelerator, causing the accelerator to decline at least some of the submitted tasks; and while the accelerator is operating at saturation, measuring by the processors accelerator performance according to a period of time during which the accelerator accepts a plurality of submitted tasks.